Vaccination of Elderly People Affected by Chronic Diseases: A Challenge for Public Health - Francesco Paolo Bianchi; Silvio Tafuri (Vaccines, 2022)
Elderly people have a limited regenerative capacity and are more susceptible to disease, syndromes, injuries, and illnesses than younger adults [...]